Entrepreneurship and innovation lab : a proposal for the enhancement of an entrepreneurial profile in undergraduate students - Repellin Moreno, Adriana Agnes; Mendieta Jiménez, Bertha Alicia (My University, 2017)
An ageing society, the development of a computational world through artificial intelligence, a new media ecology and superstructured organizations in a globally connected world, are some of the main drivers of change form the fourth industrial revolution and reshape the future workforce landscape, according to a foresight study from the Institute for the Future (2011). Likewise, the World Economic Forum (2016), states that skills such as negotiation, service orientation, critical thinking, judgement and decision making, emotional intelligence, co-ordinating with others, creativity and complex problem solving are some of the most relevant for the workforce in the future economic context. Furthermore, such skills define an entrepreneur, thus entrepreneurial education becomes even more meaningful for a student’s undergraduate experience. For the purposes of this study, we understand entrepreneurial education as the initiatives that seek to prepare responsible and entrepreneurial people, with the necessary knowledge, skills and attitudes to reach their established goals for a meaningful life (European Union, 2015). This profile makes university students versatile professionals, to become entrepreneurs, or change agents through employment. For this reason, Universidad Panamericana at Mexico City seeked to develop an entrepreneurial education project to enhance the students’ academic preparation. The Entrepreneurship and Innovation Lab was thus created, for the purpose of strengthening the students’ knowledge and skills for successful entrepreneurship, by scaling their academic projects to entrepreneurial plans. The learning experience designed to achieve this goal, included interdisciplinary teams of students from 5 different majors. They worked through an online introductory course, a networking space, and two “lab days” of conferences and workshops to explore topics such as value proposition, business model, innovation strategy, financial structure, technological routes, communication and planning, leadership and social responsibility. This study aims to explore the experience of the students that participated in the first edition of the Entrepreneurship and Innovation Lab, and how it helped them strengthen their entrepreneurial skills. Research was conducted through a qualitative approach, with individual interviews and focus groups. Results show how students valued the possibility to scale up their own academic projects to entrepreneurial plans, work with interdisciplinary student teams, and receive practical guidance from entrepreneurship experts. Students also shared how they learned to deeply understand the problems they were interested in, and validate their propositions through a practical approach. As a final result, this study proposes effective strategies to develop entrepreneurial profiles in undergraduate studies and recommendations for the design of learning experiences.